Strategi Kepemimpinan Kepala Madrasah Dalam Meningkatkan Mutu Pembelajaran Di MIS Misbahul Arifin - Rena Syahputri, Ahmad Zaki, Diyan Yusri (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2023)
Based on the results of initial observations made by researchers at the research location, information was obtained that the leadership of the madrasah head had run optimally, that is, the madrasah head played an active role in implementing learning activities by guiding the implementation of management to improve the quality of learning. The leadership of the madrasah head has been running effectively, namely with the implementation of supervision by the madrasah head both supervision of learning and teaching activities in the classroom and supervision of the madrasa head over the operational activities of teaching teachers. The leadership strategy for the head of the madrasa has been optimal, namely by implementing planning, implementing and acting on learning management in improving the quality of learning at MIS Misbahul Arifin Pangkalan Brandan. Based on the results of these observations, the researchers used qualitative research methods to describe research results based on observations, interviews and documentation. After carrying out the series of research stages, the researcher concluded that the information about the leadership of the head of the Misbahul Arifin Sei Bilah Private Madrasah Ibtidaiyah was based on the results of observations and interviews that the author conducted with informants, namely subject teachers and class teachers at the Misbahul Arifin Sei Bilah Private Madrasah Ibtidaiyah so that came to the conclusion that the head of the Madrasah Ibtidaiyah Private Misbahul Arifin Sei Bilah had carried out his duties and roles truthfully and was supported by documentary evidence of the implementation of the leadership of the head of the Madrasa as responsibility for the position.